Dissemination and Training of Identification and Development of Sport Talent for Physical Education Teachers and Sports Trainers in the Province of West Sumatra - Atradinal Atradinal; Risky Syahputra; Oktarifaldi Oktarifaldi; Romi Mardela; Lucy Pratama Putri; Irfan Oktavianus; Sari Mariati; Zainul Johor; Syahrial Bakhtiar (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
In many sporting events that have been held both nationally and internationally, Indonesia is still ranked below. Observations that have been made on PJOK teachers and trainers have found that they have not been able to identify and develop sports talent optimally by applying science. Research that has been done proves that an athlete is not only born but is also created through an appropriate talent identification program. There are at least two instruments that can be used to identify children's talents, namely I do and I Like. This application I like is online and saves and processes the data of children that we input and then will provide an output in the form of a dominant sport that is suitable for children. While I do in the form of tests of the ability of children with predetermined instruments. This service activity aims to: a) have skills in identifying and developing talent, b) understand and be skilled in using I do and I like instruments as part of talent identification, c) able to implement the management of talent identification instruments in their respective places. The method used uses the principle that every innovation received by PJOK teachers and trainers through PIE (Preparation, Implementation and Evaluation). This means that the delivery of innovations to Partners is taken through the stages of explanation, discussion, practice and evaluation stages are carried out with assistance in the learning and training process